P47 Accuracy of athlete single leg test on biodex balance system and y-balance for distinguising individuals with chronic ankle instability. (17th September 2017) - Vallabhajosula, S; Freund, J; Manning, S; Fadool, M; Groulx, D; Wikstrom, EA
Abstract : Study Design: Cross-sectional. Objectives: To determine the accuracy of athlete single leg test on the Biodex balance system (BBS) and Y-balance test in distinguishing individuals with chronic ankle instability (CAI) from healthy controls. Background: Lateral ankle sprains are common orthopaedic injuries that often result in chronic ankle instability characterised by many residual symptoms. Single leg standing test and Y-balance are commonly used to assess postural control in individuals with CAI. However, the accuracy of these tests for distinguishing individuals with CAI from healthy controls are unknown. Methods and Measures: Eighteen individuals with unilateral CAI (age=22.4±2.8 years; IdFAI=21.3±8.3), 15 individuals with unilateral injury who are copers (age=22.4±3.2 years; IdFAI=7.3±2.5), and 18 healthy controls (age=22.2±3.0 years; IdFAI=2.9±3.1) participated. Everyone completed two 20 s trials of athlete single leg testing without visual feedback at Levels 4, 8, 12, and static levels on the BBS. Each level corresponded to the degree of tilt of the platform surface with a lower number corresponding to lesser stability. Overall stability index (OSI) and sway area was calculated for each level. Maximum reach values of three trials for 3 directions (Anterior, postero-medial and postero-lateral) were recorded and used to calculate the composite score for the Y-balance test. Accuracy was quantified using area under curve from ROC curve analysis. Results: Comparing CAI and controls, the accuracy ranged from 0.213 for Y-balance composite score (indicating failure to accurately distinguish CAI from Controls) to 0.62 for sway area at Level 8 (indicating poor accuracy). Comparing CAI and Copers, the accuracy ranged from 0.389 for OSI at Level 12 (indicating failure to accurately distinguish CAI from Copers) to 0.60 for sway area at Level 8 (indicating poor accuracy). Conclusion: Athlete single leg testing on BBS and Y-balance test seem to have poor diagnostic accuracy in distinguishing individuals with CAI from healthy controls.